Effects of temperature and coating treatment on gas exchange of 'Braeburn' apples : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science at Massey University - Cheng, Qingmin (Massey University, 1999)
Achieving modified atmosphere (MA) effects on fruit through the use of surface coatings relies upon a suitable degree of internal atmosphere modification, which is strongly dependent upon both respiration rate and skin permeance to gases. In this study, skin porosity, skin permeance, internal partial pressures of oxygen and carbon dioxide, and respiration rate were measured at 0°C, 10°C, 20°C and 30°C in non-coated 'Braeburn' apples. Variation in respiration rate, internal partial pressures of oxygen and carbon dioxide, skin permeance to oxygen and carbon dioxide, and the extent to which all of these gas exchange characteristics affected by temperatures of 0°C, 5°C, 10°C, 15°C, 20°C were characterised in both non-coated and coated 'Braebum' apples. Coating treatments were 0, 0.2, 0.4, 0.6, 0.8 and 1.0 times either a 2% (w/w) solution of hydroxypropylcellulose (HPC) in distilled water, or a commercial formulation of carnauba wax and shellac coating, achieved by mixing the full strength solutions with distilled water. There was a 6- or 10-fold difference in respiration rate between fruit kept at 0°C and 20°C, or 0°C and 30°C, whilst the relative permeance to both O 2 and CO 2 differed only a factor of 1.7 or 1.5 in non-coated fruit. The differing effects of temperature upon these two variables were responsible for the depression of internal O 2 and elevation of internal CO 2 associated with increase in temperature from 0°C to 20°C or 30°C. There was no evidence that porosity was dependent on temperature, suggesting that the increasing permeance with higher temperatures may have resulted from increasing permeance of the cuticle. The modification of internal atmosphere composition in carnauba-coated fruit depended upon coating concentration and temperature. The effects of HPC coating on internal atmosphere, especially on internal CO 2 were less marked than those of temperature. In non-coated fruit, the magnitude of decline in internal O 2 was slightly greater than the increase in internal CO 2 over the temperature range in the experiment. For apples that were respiring aerobically, this indicates that the fruit skin had a slightly higher permeance to CO 2 than to O 2 . Since O 2 diffuses through pores were readily than CO 2 , gas exchange of these fruit appeared not to be pore dominated. The suppression of gas exchange by shellac coating was consistent with the coating blocking pores on the fruit surface to an extent that depended on coating concentration. The less pronounced effects of HPC coating in both skin permeance and internal gases were consistent with a coating that loosely covered the fruit surface rather than blocking the pores. Low concentrations of shellac coating achieved low internal O 2 levels at higher temperatures but had only slight effects on internal atmosphere composition at low temperatures. Higher concentrations that achieved MA benefit at low temperatures resulted in fermentation at higher temperatures. Given the natural variability in skin permeance, and the exacerbating effects of coating treatment and temperature, surface coatings appear unlikely to provide a reliable and safe means of achieving modified atmosphere benefits in 'Braeburn' apples.
Keywords: Apples; Postharvest technology; Postharvest physiology; Effect of temperature on